Use of a novel semi-derotation technique for artery-first approach in laparoscopic pancreaticoduodenectomy. (June 2020) - Kiguchi, Gozo; Sugioka, Atsushi; Kato, Yutaro; Uyama, Ichiro
Highlights: LPD remains one of the most advanced laparoscopic procedures. A novel semi-derotation technique was developed based on the complex anatomical features around the pancreatic head. This technique is a new strategy for simplifying anatomic situation around SMA by derotating the rotation of the mesentery. The key with this technique is to cut the "Gordian anchor". This video shows the concept and procedures of the semi-derotation technique.